Sociodemographic Factors and Contraceptive Use Duration Prior to Discontinuation: A Cross-Sectional Study [Accepted] - Kristianti, Shinta; Budihastuti, Uki Retno; Febrinasari, Ratih Puspita (Health Dynamics, 2026)
Background: Discontinuation of contraceptive use among women of reproductive age can hinder the attainment of the Sustainable Development Goals (SDGs). Sociodemographic factors of women may be related to the contraceptive use duration before they decide to discontinue. It can be used as a basis for formulating interventions to ensure they are on target. The aim of this research to identify and analyze the association between sociodemographic factors and duration of last contraceptive use among women of reproductive-age who ever had experienced discontinuity of their contraception. Methods: The study was a cross-sectional, women aged 20-49 years who ever experienced contraceptive discontinuation as the population. Sampling based on purposive stratified random sampling with proportional allocation obtained a sample of 150 people. The study was conducted in Kediri Regency which was carried out in August-September 2025. Age, education, employment status, number of children, and the last contraceptive method used when discontinuing use were observed as independent variables. The duration of the last contraceptive use for the dependent variable. Primary data collection used a questionnaire and was analyzed using Spearman's Rho test. Results: Research outcomes presented a significant relationship between women’s age and the duration of last contraceptive use (p = 0.007).Conclusions: The correlation between women’s age and duration of last contraceptive use can be used as a basis for developing interventions to extend the duration of contraceptive use through comprehensive and ongoing education or counselling about the benefits and management of side effects of contraception in younger mothers.